2005
DOI: 10.1017/s0022029904000457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different milking routines on milking-related release of the hormones oxytocin, prolactin and cortisol, and on milk yield and milking performance in Murrah buffaloes

Abstract: Milking-related release of oxytocin, prolactin, and cortisol was studied following three pre-milking treatments. Six Murrah buffaloes were treated with direct application of milking cluster (O), a 1-min pre-stimulation (M), and combined feeding and pre-stimulation (MF). Machine milk yield, stripping yield and milk composition were recorded. Milk ejection occurred significantly earlier with MF than M and O (P<0·05; 2·50, 5·10 and 6·33 min, respectively). In all treatments, milk ejection occurred with small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
1
35
2
3
Order By: Relevance
“…In our experiment the time elapsed from attachment of the milking cluster until its automatic removal was less than 8 min both for buffaloes subjected to fast pulsation, and for buffaloes subjected just to washing of the teats before attaching the milking unit. This value is markedly lower if compared with manual removal of the teat cups (Thomas et al, 2005;Bava et al, 2007;Caria et al, 2011), confirming that the operator's choice to not use automatic cluster removers, as frequently occurs in dairy buffaloes milking, strongly influences the milking time. In buffaloes milked by AMS the milking duration averaged 8.3±2.7 min (Caria et al, 2014), even if in that case it was calculated as the time between the buffalo identification and the last teat-cup detachment.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…In our experiment the time elapsed from attachment of the milking cluster until its automatic removal was less than 8 min both for buffaloes subjected to fast pulsation, and for buffaloes subjected just to washing of the teats before attaching the milking unit. This value is markedly lower if compared with manual removal of the teat cups (Thomas et al, 2005;Bava et al, 2007;Caria et al, 2011), confirming that the operator's choice to not use automatic cluster removers, as frequently occurs in dairy buffaloes milking, strongly influences the milking time. In buffaloes milked by AMS the milking duration averaged 8.3±2.7 min (Caria et al, 2014), even if in that case it was calculated as the time between the buffalo identification and the last teat-cup detachment.…”
Section: Resultsmentioning
confidence: 78%
“…The application of an attachment delay of 60-90 s after stimulation before milking is recommended to ensure immediate and continuous milk flow after the start of milking in dairy cows (Rasmussen et al, 1992). Thomas et al (2005) found that milk ejection in Indian Murrah buffaloes occurred significantly earlier for machine milking with in-parlour feeding and 1-min manual pre-stimulation (washing, drying and short massage of teats) than for machine milking without manual pre-stimulation or in-parlour feeding. This highlighted that a careful teat preparation and pre-stimulation are important preconditions for successful milk removal also in dairy buffaloes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations